Analisis Potensi Risiko Kerja Pada Unit Bisnis Kontruksi Piping Dengan Metode HIRADC Pada PT XYZ - Rendhi Trio Hutomo1; Wahyudin; Sukanta (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This research was conducted at PT XYZ with the focus of the research being one of its business units, namely piping construction services. This research is descriptive quantitative research, namely explaining the analysis of the implementation of occupational safety and health in the pipe construction business unit of PT XYZ. Data collection techniques were observation, documentation, interviews and distributing questionnaires to 30 workers with the method used was the HIRADC method. This research aims to identify potential work hazards, assess risk levels, and analyze efforts to control potential work risks. The research results show that there are 27 potential work risks with 13 work potentials in the low category, 7 work potentials in the medium category, and 7 work potentials in the high category. Efforts to control work risks from the results of the analysis are by conducting safety briefing procedures, giving warnings if you do not use PPE and providing PPE that is not yet available, conducting work site inspections, ensuring work procedures and safety procedures (SOP), determining appropriate testing procedures, and providing workpiece tools.